Combination of glass produce artistic wall lamp / Salmah Ali … [et al.] - Ali, Salmah; Hamzah, Azni Hanim; Ab Aziz, Nurul Izza; Abdulah, Nur Hasliza; Dasuki, Shaliza (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Glass existed in various forms in our life especially domestic and table wares. In addition, glass is also used as one of the mediums for art media, since many forms could be created using glass to produce three-dimensional sculpture, instead of just bowl, vase and using glass for building construction or even kitchen utensils (Cooke, 1986). The product also focuses on the best combination of two types of glass; Heat Absorbing Float glass (multicolor) and flora glass (green, blue and yellow.), as the main materials and joining rod, plate on mild steel structure also lighting to create artworks. The combination of a few types of glasses includes fusing, slumping and casting technique, which in fact commonly used among glass men or glass artists. Three main approaches have been conducted. First exploring glass surface based on three glass techniques for manipulation of texture and color. Secondly recognizes melting point for each types of glass especially uses for creating glass surface for th is product and finally selected glass samples using lighting. Based on the three approaches above, experiments have successfully produced 58 samples. The result shows that combination of glass was the best effect on beam glass to bulbs lamp or sunlight.